Meningkatkan Kemampuan Public Speaking bagi Generasi Muda Di Desa Tebing Sari Kecamatan Belitang Madang Raya - Agustina, Eka; Kurniati, Nia; Maslena, Mega; Rofiqah, Siti Anisatur (Jurnal Indonesia Mengabdi, 2021)
The objective of this program to give knowledge of English, to motivate children in Tebing Sari village to be more enthusiastic in learning English and give confidence to children to speak in English. Based on the teaching process in this program, it can be seen that the children gave a positive response by joining the regular learning schedule, their speaking skills improved and they could confidence to speak in English in public.